The autoimmune disease risk variant NCF1-His90 is associated with a reduced risk of tuberculosis in women - Xinjun Hu; Shasha Li; Renliang Huang; Ziwei Fu; Chenyu Ma; Zheng Cheng; Hongjun Hu; Qiaomiao Zhou; Frank Petersen; Xinhua Yu; Xinhua Yu; Junfeng Zheng (Frontiers in Immunology)
IntroductionThe neutrophil cytosolic factor 1 (NCF1) rs201802880 polymorphism is a missense mutation resulting in an amino acid substitution from arginine to histidine at position 90, which impairs the function of NADPH oxidase. This casual variant confers an increased risk for multiple autoimmune disorders, including primary Sjögren’s syndrome and systemic lupus erythematosus. Given the high prevalence of this autoimmune disease risk variant in East Asia, we hypothesized that it may confer an evolutionary advantage by providing protection against infectious diseases.MethodsTo test this hypothesis, we investigated whether the NCF1 rs201802880 variant offers a protective effect against tuberculosis (TB), a historically significant and deadly infectious disease. Our study included 490 healthy controls and 492 TB patients who were genotyped for the NCF1 rs201802880 polymorphism.ResultsOur results showed that the NCF1 rs201802880 AA genotype was associated with a reduced risk of TB in women (OR= 0.25, 95% CI: 0.09-0.68, p=0.0023). Additionally, healthy individuals with the NCF1 rs201802880 AA genotype had significantly lower circulating white blood cell (5.56 ± 1.78 vs 6.43 ± 1.59, p=0.003) and neutrophil (3.23 ± 1.20 vs 3.74 ± 1.23, p = 0.02) counts compared to those with the GG or GA genotypes, with this difference being more pronounced in women than in men.ConclusionThis study demonstrates that the autoimmune disease-causal NCF1 variant is associated with a protective effect against TB infection.